TIGA LANDASAN FILSAFAT PENDIDIKAN : ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI - Istikomah, Yayuk; Sofiatunnaimah, Eni; Abi Auafa, Ari (As-Sulthan Journal of Education, 2025)
Philosophy of education plays a crucial role in providing a strong conceptual foundation for the implementation of education. This paper examines the three main foundations of the philosophy of education, namely ontology, epistemology, and axiology, as a philosophical framework for understanding and developing educational practice. Ontologically, education is viewed as a process of humanization based on the nature of learners as beings who possess holistic potential, including physical, intellectual, emotional, social, and spiritual aspects. Epistemologically, education is understood as a process of searching for and developing true knowledge through experience, rational thinking, critical attitudes, and interaction with the environment, so that learners are not merely passive recipients of information but active subjects in constructing knowledge. Axiologically, education is directed toward the formation of values, morals, and character so that the knowledge acquired can be used responsibly for the benefit of life. This study employs a library research method by reviewing various relevant references. The findings indicate that the integration of ontology, epistemology, and axiology produces a holistic, adaptive, and value-oriented concept of education, enabling learners to become intelligent, virtuous, and responsible individuals in both personal and social life.